A universal recombinant adenovirus type 5 vector-based COVID-19 vaccine - Li, Xingxing; Peng, Qinhua; Liu, Xinyu; Xu, Hongshan; Liu, Jingjing; Wu, Xiaohong; Ye, Qiang; Li, Min; Li, Yuhua (Frontiers in Immunology, 2024)
A universal recombinant adenovirus type-5 (Ad5) vaccine against COVID19 (Ad-US) was constructed, and immunogenicity and broad-spectrum of Ad5-US were evaluated with both intranasal and intramuscular immunization routes. The humoral immune response of Ad5-US in serum and bronchoalveolar lavage fluid were evaluated by the enzyme-linked immunosorbent assay (ELISA), recombinant vesicular stomatitis virus based pseudovirus neutralization assay, and angiotensin-converting enzyme-2 (ACE2) -binding inhibition assay. The cellular immune response and Th1/Th2 biased immune response of Ad5-US were evaluated by the IFN-γ ELISpot assay, intracellular cytokine staining, and Meso Scale Discovery (MSD) profiling of Th1/Th2 cytokines. Intramuscular priming followed by an intranasal booster with Ad5-US elicited the broad-spectrum and high levels of IgG, IgA, pseudovirus neutralizing antibody (PNAb), and Th1-skewing of the T-cell response. Overall, the adenovirus type-5 vectored universal SARS-CoV-2 vaccine Ad5-US was successfully constructed, and Ad5-US was highly immunogenic and broad spectrum. Intramuscular priming followed by an intranasal booster with Ad5-US induced the high and broad spectrum systemic immune responses and local mucosal immune responses.